Brand crisis response strategies: a typologies continuum - Do, Bich Ngoc; Nham, Tuan Phong (Business: Theory and Practice, 2021)
This purpose of this study is to provide a spectrum to illustrate all applicable response strategies towards brand crisis management. A qualitative systematic method is adopted to review 128 relevant papers and synthesized in a brand crisis response typologies continuum. The findings were illustrated in the continuum which includes two main categories – primary response group with seven levels ranked lowest to highest by organizational involvement and responsibility, and secondary response group such as bolstering). This research result might enrich the current literature of brand crisis management which is fragmented and provide a clear guideline so that scholars and practitioners might track all pertinent solutions depending on low to high level of brands’ effort towards handling problems. Recognizing the discrepancy among response strategies, marketers and branders can choose either singular or merged solutions shown in the map to form a timely response to brand crisis, which is the main factor to crisis response success.